Estudo da inativação microbiana em água utilizando um reator UV-C - Santos Filho, Generoso de Jesus (Universidade Federal de São Carlos, 2023)
Water has a direct influence on health, quality of life and human development. Most of the infectious disease burden in developing countries refer to water contamination by pathogenic microorganisms, emphasizing the importance of proper treatment, even in point-of-use solutions. Ultraviolet C radiation (UV-C) as a germicide has been studied since the beginning of the 20th century. Microorganism inactivation by UV-C is caused by alterations in DNA that lead to the formation of the pyrimidine dimer. In this study, the performance of a UV-C reactor coupled to a storage tank was evaluated, aiming to disinfect water artificially seeded with Escherichia coli. The prototype consisted of a closed-circuit system, with continuous flow, able to operate with different storage volumes. In the system, water circulates by mechanic agitation impelled by two peristaltic pumps. The UV-C irradiation source was based on 6 units of 30 W germicide lamps. In this study, operation was investigated in different volumes (1, 2, 5, and 15 L), under constant flow rate of 1 L/min of fluid exposure to light, for 60 min maximum. Finally, an analysis was carried out considering the empirical relationships found, to allow extrapolate results aiming to determine the required time to remove a given concentration of E. coli in different volumes of water. The effect of germicidal lamps on microbial inactivation showed that there is a bacterial reduction in different volumes, since in the experiments carried out the initial concentration of E. coli in logarithmic scale in volumes 1, 2, 5 and 15 L were 7.13, 5.74 , 6.10 and 5.78 log CFU/mL, respectively. The analysis shows us that in volumes 1, 2, 5 and 15 L there was a reduction in E. coli survival of 6.24, 4.03, 2.78 and 1.64 log CFU/mL, respectively.
Study of microbial inactivation in water using a UV-C reactor
Keywords: Descontaminação; Escherichia coli; Ponto de uso; Tratamento descentralizado; Decontamination; Escherichia coli; Point-of-use; Decentralized treatment; CIENCIAS BIOLOGICAS; 6. Água Potável e Saneamento